Recent Advances in Spinel Ferrite-Based Thin Films: Synthesis, Performances, Applications, and Beyond - Hao, Aize; Ning, Xueer (Frontiers in Materials, 2021)
This review provides a comprehensive review of the recent advances in the various typical spinel ferrite-based thin films with controlled synthesis, its performances, applications in multifunctional material fields, and fundamental scientific challenge and beyond. Firstly, the crystal structures of spinel ferrite-based thin films are introduced. Secondly, recent progresses in traditional synthesizing and novel methods for preparation of spinel ferrite-based films have been highlighted. Thirdly, its magnetism, electricity, optics performances and applications in advanced information technology, energy storage and conversion, and environmental conservation fields have also been summarized and discussed in depth. Some eﬀective strategies for optimizing performances and further applications are summarized. Finally, the present review work ends with a short discussion concerning the challenges, opportunities and future prospect of spinel ferrite-based thin films.